Organoleptic Assessment of the Performance of Some Cultivars of Ipomoea batatas in the Development of Selected Snack Products - Ojinnaka, M.C.; Onwuka, G.I. (Pakistan Journal of Nutrition, 2011)
Baking tests were conducted with sweet potato (Ipomoea batatas) composite paste at 20% level of substitution with wheat flour to determine their potentials in producing acceptable snack products. Studies conducted shows there was no significant difference (p>0.05) in the specific volume of the baked bread samples but there was significant difference (p